Improving SARS-CoV-2 variants monitoring in the absence of genomic surveillance capabilities: a serological study in Bolivian blood donors in October 2021 and June 2022 - Lucia Inchauste; Elif Nurtop; Lissete Bautista Machicado; Yanine Leigue Roth; Shirley Lenz Gonzales; Maria Luisa Herrera; Katty Mina Villafan; Pedro Mamani Mamani; Marcelo Ramos Espinoza; Juan Carlos Pavel Suarez; Juan Cansio Garcia Copa; Yitzhak Leigue Zabala; et al. (eLife, 2025)
Background: Unlike genomic data, serological data have not been previously leveraged to evaluate the SARS-CoV-2 variants circulation. In Bolivia, sustained genomic surveillance capacities were lacking, especially at the beginning of the pandemic. Methods: In 2021 and 2022 we estimated the prevalence of anti-SARS-CoV-2 antibodies in Bolivian blood donors and explored the feasibility of using virus serum neutralization data for variants thought to have circulated to map their circulation across all departments over a year-long follow-up period. Anti-S1 and anti-NCP SARS-CoV-2 IgGs were studied, along with virus neutralization tests for ancestral-D614G, Gamma, Delta, and Omicron BA.1 lineages of SARS-CoV-2. Results: Between 2021 and 2022, the overall prevalence of anti-S1 and anti-NCP antibodies increased, reaching values over 90%, demonstrating that a large proportion of the Bolivian population was no longer naïve to the virus. Viral neutralization data, analyzed through multiple approaches, revealed the spread of the Gamma variant up to 2021, particularly impacting northern departments. In 2022, Gamma continued to circulate in southernmost departments of the country, and the emergence of Omicron BA.1 was detected. These trends align with publicly available genomic data from neighboring countries. Conclusions: Our serological analyses successfully identified both new antigenic groups, such as Omicron BA.1, and individual variants related to previously circulating groups, such as Delta. The study contributes insights into overall population immunity to SARS-CoV-2 and variant-specific immunity levels across different regions of Bolivia. It also emphasizes the potency of seroprevalence studies in informing public health decisions and underscores their value in capturing the initial phases of emerging epidemics when variant diversity is limited, facilitating timely genomic surveillance setup. Funding: This study was supported by the French National Research Institute for Sustainable Development (IRD), the project EMERGEN-PRI #22275 of the ANRS I MIE (INSERM), and the European Union’s Horizon 2020 research and innovation program (European Virus Archive Global, grant agreement No. 871029). The funders of the study had no role in study design, data collection, data analysis, data interpretation, or writing of the report.